INSTAGRAM @ INDONESIABAIK.ID ACCOUNT MANAGEMENT STRATEGY AS A MEDIUM FOR DISSEMINATING PUBLIC INFORMATION - Larasati, Sri Dewi; Kartikawati, Dwi (International Journal of Social Service and Research, 2024)
Social media is a platform that allows users to engage in interaction, collaboration, and the formation of virtual social communities. Social media plays an important role in the dissemination of information. This research aims to study how to manage Instagram accounts owned by the Indonesian government, namely, Indonesian accounts belonging to Kominfo. The research uses a qualitative approach to gather in-depth narratives and detailed accounts from informants. The data was collected through interviews, observations, and literature studies. Finally, the data was interpreted to answer the research questions and provide meaningful insights. This study contributes to understanding the effective management of social media platforms, specifically Instagram, as a tool for disseminating public information. The study provides insights into strategies and practices that can optimize social media usage for public communication, enhancing engagement, information accessibility, and public awareness. This could provide further insights into optimizing social media strategies for public information dissemination.